Canadian clinical practice guidelines for the use of plant-based cannabis and cannabinoid-based products in the management of chronic non-cancer pain and co-occurring conditions: protocol for a systematic literature review. Issue 5 (24th May 2020) - Wright, Patrick; Walsh, Zach; Margolese, Shari; Sanchez, Tatiana; Arlt, Stephanie; Belle-Isle, Lynne; St.Pierre, Michelle; Bell, Alan; Daeninck, Paul; Gagnon, Marilou; Lacasse, Gary; MacCallum, Caroline; et al.
Abstract : Introduction: Chronic pain and co-occurring disorders, such as sleep disorders, anxiety, depression, post-traumatic stress disorder and substance use disorders, are among the most common conditions for which cannabis and cannabinoid-based products derived from the cannabis plant (CBP) are used for therapeutic purposes. However, healthcare providers report that they lack sufficient information on the risks, benefits and appropriate use of cannabis and CBP derived from the cannabis plant for therapeutic purposes. Methods and analysis: We will conduct a systematic review of studies investigating the use of cannabis and CBP derived from the cannabis plant for the treatment of chronic pain and co-occurring conditions. Randomised controlled trials, meta-analyses and observational studies will be prioritised. We will exclude reviews of cannabinoid mechanisms of actions, commentary articles and narrative reviews. The primary outcome of interest will be efficacy in relieving chronic pain. Secondary outcomes will be efficacy in ameliorating conditions such as sleep disorders, anxiety, depression, post-traumatic stress disorder and substance use disorders. We will search electronic bibliographic databases including Academic Search Complete, Cochrane Database of Systematic Reviews, Evidence based Medicine Reviewes, OVID Medline, PsychINFO, PubMed, CINAHL and Web of Science. Two reviewers will conduct screening and data collection independently. Study level of bias will be assessed using the Cochrane Risk of Bias Assessment Tool for randomised controlled trials and non-randomised studies. Narrative analysis will be utilised to interpret the data. Ethics and dissemination: The results of this systematic review will inform guideline development for the use of cannabis and CBP derived from the cannabis plant in the management of chronic pain and co-occurring conditions. Areas requiring further study will also be highlighted. PROSPERO registration number: CRD42020135886.